Analysis Of High Quality Agarwood Oil Chemical Compounds By Means Of Spme/Gc-Ms And Z-Score Technique - Saiful Nizam, Tajuddin; Nurlaila, Ismail; Mohd Ali, Nor Azah; Mailina, Jamil; Mohd Hezri, Fazalul Rahiman; Mohd Nasir, Taib (Universiti Kebangsaan Malaysia, 2013)
Currently, the grading of the agarwood oil to the high and low quality is done using manually such as human trained grader. It was performed based on the agarwood oil physical properties such as human experience and perception and the oil colour, odor and long lasting aroma. Several researchers found that chemical profiles of the oil should be utilized to overcome the problem facing by manual techniques i.e. human nose cannot tolerate with the many oils at the same time, so that accurate result can be obtained in grading the agarwood oil. The analysis involved of SPME/GC-MS and Z-score techniques have been proposed in this study to analyze the chemical compounds especially from the high quality samples of agarwood oil (Aquilariamalaccensis) from Malaysia. Two SPME fibers were used such as divinylbenzene-carboxen-polydimethylsiloxane (DVB-CAR-PDMS) and polydimethylsiloxane (PDMS) in extracting the oils’ compound under three different sampling temperature conditions such as 40˚C, 60˚C and 80˚C. The chemical compounds extracted by SPME/GC-MS were analyzed. The chemical compounds as identified by Z-score as significant compounds were discussed before the conclusion is made. It was found that 10-epi-ϒeudesmol, aromadendrane, β-agarofuran, α-agarofuran and ϒ-eudesmol were highlighted as significant for high quality agarwood oil and can be used as a marker compounds in classifying the agarwood oil.